PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN DESA WISATA BUDAYA DAN SEJARAH DI DESA PARIANGAN - Oksavira, Alfadiya Rizki; Maryani, Enok; Andari, Rini (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study investigates the role of community empowerment in developing cultural and historical tourism villages in Pariangan Village, located in Tanah Datar Regency, West Sumatra. Data was collected from 151 respondents, consisting of local and foreign individuals, using a quantitative approach. To ensure the accuracy of the data, the research instruments were tested for validity and reliability. The research results indicate that the development of tourism villages is significantly influenced by community empowerment, which includes active community participation, the formation of business groups, training, and government support. In addition to contributing to the preservation of culture and the environment, this empowerment also increases the income and well-being of the local community. According to regression analysis, community empowerment is a very strong predictor of tourism village development (? = 0.989; p < 0.001). These results indicate that communities must be involved in sustainable tourism development. Therefore, tourism village development strategies should focus on enhancing the capabilities of local communities and increasing their participation.